HUBUNGAN LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN ISPA PADA BAYI - Vedjia Medhyna (Maternal Child Health Care, 2019)
Acute Respiratory Infection it still is one of cause of death in infants in Indonesia. Acute Respiratory Infection in the infant influence many factor. The purpose of this study is to define the correlation of environment with  ARI at the Health Care in Pasaman Region.This study used prospektive design, the collection of data usingobservational against 175 infants as a sample to find out the house ventilation, the floor type, kitchen ventilation, residential density, fuel used to cook and the incidence of ARI. The result of bivariat analysis shows that the factor predisposing occurence of ARI was house ventilation (p = 0,004), floors type (p = 0,035), residential density (p = 0,039), and kitchen ventilation (p = 0,038). Multivariate analysis showsthat the house ventilation is the most dominant factor (OR=3,192). The conclusion of this study was house ventilation influence of ARI, it is recommended to all health care provider to be more active providing counseling and education to community.Keywords:   the house ventilation, the floor type, kitchen ventilation, residential density, fuel used to cook, Acute Respiratory Infection